ETHICAL VIEWS OF TOTALITARIANISM IN HANNAH ARENDT’S POLITICAL PHILOSOPHY - Pykalo, Andrii O. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2019)
The article analyzes the ethical studies of Hannah Arendt on the origin of totalitarianism. The author considers the conditions for the formation of a “total state” and the role in these processes of both society as a whole and an individual. Based on the works of Hannah Arendt, the author analyzes the features of the totalitarian transformations of the individual and society, as well as their interaction with the regime at different stages of the functioning of the “total state”. According to Hannah Arendt, totalitarianism is a system of mass terror, which is a phenomenon of the twentieth century. Totalitarianism is realized in the conditions of the destruction of political space and human interaction. It is the result of the alienation of a person from political life, that is, the “atomization” of society against the background of a deformation of basic ethical standards and established ideas about morality in general. Considering the problem of the emergence of totalitarianism, Arendt turns to the anthropological plane, where she explores the way in which violence enters the public sphere, and politics turns into an instrument for achieving certain goals and serving private interests. Hannah Arendt also analyzes the phenomenon of the “banality of evil,” which lies at the base of the so-called “respectable society”. Such a society easily becomes a weapon of totalitarianism along with “grassroots executors of orders”, as the example of Adolf Eichmann demonstrates. Hannah Arendt believes that the actions of such “executors of orders” should always be assessed as the actions of a person, and not just a “social tool”, from which responsibility for crimes is thus removed. Hannah Arendt identifies various areas of ethical (namely, areas of individual and public morality), where there is a division into personal and political responsibility, and also studies the problems of preventing a possible repetition of totalitarianism. The “means” for such prevention, according to Hannah Arendt, are on an ethical plane. This is, firstly, the possibility of independent judgment and critical thinking, which create personal principles. And secondly, the presence of a public sphere, which provides the possibility of free action in a common social space. This is what actualizes moral issues and ensures the formation of moral principles.